Faktor-Faktor yang Mempengaruhi Minat Masyarakat Terhadap Pembiayaan Kredit Kepemilikan Rumah (KPR) BTN - Hendri Wira; Wiwik Andriani; Fera Sriyunianti (Politeknik Negeri Padang, 2023)
According to PSAK No. 31 of 2004, banks act as institutions that have an intermediary function to manage the finances of various parties who have excess funds and those who have limited funds which also function as institutions to facilitate payment traffic. This study aims to see the effect of income level, number of dependents, education level, age, and housing location on public interest in financing BTN Home Ownership Credit (KPR) in Nagari Sungai Rumbai. The data used in this study is primary data. The data collection technique used a questionnaire distributed to the community in Nagari Sungai Rumbai. This research uses normality test, validity and reliability test, and hypothesis testing. The results showed that there was a significant effect of the variables of income level, number of family dependents, education level, age, and also the location of housing on public interest in the financing of BTN Home Ownership Credit (KPR).